Monitoring outcomes of CSA options in Doyogena Climate Smart village, Ethiopia (2019) - Bonilla Findji, Osana (2019)
CSA monitoring Training held in Hosanna-Ethiopia, Africa October 28, 2019 by the CCAFS-F2 team.